Ultra-low thermal conductivity in scheelite and A-deficient scheelite ceramics. (August 2021) - Bsaibess, Eliane; Delorme, Fabian; Monot-Laffez, Isabelle; Giovannelli, Fabien
Graphical abstract: Abstract: Synthesis of scheelite-type oxides based on lanthanum and barium molybdate (BaMoO 4 and La 2 Mo 3 O 12 ceramics) were successfully prepared via conventional solid-state reaction method. Dense ceramics were obtained by conventional sintering. Structural, microstructural and thermal properties of both sintered ceramics were assessed to identify the impact of cation deficiency on thermal conductivity. BaMoO 4 ceramic has shown a decrease in thermal conductivity from 0.8 W m − 1 K − 1 to 0.65 W m − 1 K − 1 from 400 K to 650 K. The deficient scheelite La 2 Mo 3 O 12 compound was found to further reduce thermal conductivity. An ultra-low thermal conductivity constant value of about 0.59-0.62 W m − 1 K − 1 was calculated over the entire temperature range. This value is the lowest recorded value for oxides so far discovered and such materials may be promising ones for thermal insulating applications.